Dicyandiamide-Driven Tailoring of the n-Value Distribution and Interface Dynamics for High-Performance ACI 2D Perovskite Solar Cells - Ge Chen; Yunlong Gan; Shiheng Wang; Xueru Liu; Jing Yang; Sihui Peng; Yingjie Zhao; Pengwei Li; Asliddin Komilov; Yanlin Song; Yiqiang Zhang (Nano-Micro Letters)
Highlights Guanidine derivatives of dicyanodiamide (DCD) is introduced into the buried interface of quasi-2D alternating-cation-interlayer perovskites (GA(MA)nPbnI3n+1), which simultaneously realize the defect passivation of buried interface and the regulation of phase distribution. This interface engineering not only reduces interfacial defects but also enhances the interfacial charge transfer, and the DCD-regulated perovskite solar cells exhibit a significant increase in efficiency from 19.05% to 21.54%.